MENTAL HEALTH STATUS AND DRUG USE PATTERN AMONG UNDERGRADUATES IN A NIGERIAN UNIVERSITY - Olutunde, Olatunji Samuel (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The study examined the mental health status of the undergraduates in relation to their patternof drug use. 240 students including 138 males and 102 females drawn from Ekiti StateUniversity participated in the study. General Health Questionnaire and Drug use Scale wereemployed to collect data. One Way ANOVA and independent t-test were used to test thethree hypotheses stated. Result shows that alcohol consumption has a significant effect onsomatic symptoms, anxiety and depression, but not on social dysfunction. Results also showhow undergraduates vary in their mental health status relating to somatic symptoms, anxiety,depression and social dysfunction. Findings from hypothesis three showed a significant sexdifference in drug and alcohol use but not in their mental health.